Historical interactive virtual reality learning in college - Setiawan, Risky; Nugroho, Alifi Nur Prasetia; Hadi, Kuncoro; Laksana, Novianto Yudha; Widianto, Hardian Wahyu (Program Pascasarjana Universitas Negeri Yogyakarta, 2021)
Virtual Reality provides many benefits in learning because it can create a variety of simulation situations that can not be done due to obstruction of danger or high costs. This research aims to research and develop learning media in history using virtual reality technology. This research and development use ADDIE's research steps method (analyze, design, develop, implement and evaluate). The Delphi method carried out product validation using four media experts and four historians. The product trial phase uses 400 students in two study programs to see the effectiveness of the products developed. Research & development have produced a prototype product website platform with expert feasibility assessment (product validation) results. The results of the media expert assessment are 3.88 (feasible), and the expert assessment material of 4.09 (possible). The media tested on 400 students obtained satisfactory results, with the average overall score reaching 4.23 or in the category of